Estudio de factibilidad para la fabricación y comercialización de productos en caucho reciclado de llantas usadas (adoquines de caucho, vinil de caucho, etc.) En la ciudad de Quito - Armas Cárdenas, Juan José (2013)
This feasibility study for manufacturing and commercialization products made from used tires (rubber paving stone, rubber, vinyl, and so on) in the city of Quito is aimed to encourage the Quiteña industry to create new manufacturing processes through waste reuse which can help significantly with this country’s development, and it will especially contribute to the environment's preservation. In the introduction study it was possible to prove that there is a big amount of waste produced by the automotive growth, which is very worrying, but at the same time it is helpful for this project due to the fact that the automotive rubbish is the raw material which will be transformed into innovative rubber paving stone and vinyl.